2017
DOI: 10.1002/cbm.2058
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of current policing‐related mental health interventions: A systematic review

Abstract: Overall, rather than indicating that one approach is more effective than another, the review points to the need for a multi-faceted approach within a structured and integrated model, such as the CIT model. This is generally not the current pattern of interventions, and policy makers, service commissioners and providers may wish to review future options. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
1
49
0
3
Order By: Relevance
“…We identified individuals who had been triaged through the CCR embedded MH professionals. Use of these staff has grown since the mid‐2000s, but a systematic review (Kane et al, ) indicated that their use has yet to be evaluated through high quality studies that would provide a context and comparison for our findings. It would be reasonable to assume that CCR embedded staff involvement would influence the initial response made by the police.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified individuals who had been triaged through the CCR embedded MH professionals. Use of these staff has grown since the mid‐2000s, but a systematic review (Kane et al, ) indicated that their use has yet to be evaluated through high quality studies that would provide a context and comparison for our findings. It would be reasonable to assume that CCR embedded staff involvement would influence the initial response made by the police.…”
Section: Discussionmentioning
confidence: 99%
“…The model provides for a core team, which is almost always staffed by psychiatric nurses, and an extended team with staff from various agencies that play key roles in diversion, including housing and welfare specialists (Kane, Evans, & Shokraneh, 2018).…”
Section: The Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriateness of diversion is likely to be based on the seriousness of the offence, the safety of the individual and the public (DeMatteo, LaDuke, Locklair, & Heilbrun, 2013). The appeal of prearrest diversion lies in its promise for reducing criminal recidivism in the longer term, enhancing public safety, saving money, and improving access to the appropriate services for people with mental health problems (Heilbrun et al, 2012;Kane, Evans, & Shokraneh, 2018). There has, however, been no systematic evaluation of research to date which has assessed such outcomes, so prearrest diversion is still not deemed to be evidence-based (Watson, Compton, & Draine, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Health Screening of People in Police Custody (HELP‐PC) project, for example, has produced an evidence‐based screen that can be simply applied; however, in most areas, appropriate screening is simply not being done (McKinnon & Grubin, ). Meanwhile, attempts to help police by flagging risk may be disadvantaging the people with mental disorder who come into contact with them (Kane, Evans, & Shokraneh, ).…”
Section: Resultsmentioning
confidence: 99%